Determination of Production and Marketing Behaviors of Producers Selling Products to the Turkish Grain Board, (Kırşehir Province Mucur District Micro Field Study) - Hasan Gökhan Doğan; Aybüke Bulut (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study is to examine the socio-economic characteristics of producers who sell wheat to the Turkish Grain Board (TGB), which is an interventionist organization in the purchase and sale of grain in Türkiye, as well as some of their behaviors regarding production, marketing preferences, and their relations with TGB. The sample of the study consisted of 100 wheat producers in the Mucur district of Kırşehir province. The obtained data were interpreted by converting them into tables, cross-tabulations, and graphs. The data in the cross tables were statistically interpreted using Chi-square analysis. It can be said that producers are not satisfied with TGBs’ purchasing practices for some reasons. The most important reason for this is that quality-based purchasing practices have an extremely negative impact on prices. It was determined that they were not satisfied, and this resulted in high price reductions in quality-based purchasing, and as a result, there was distrust in analysis practices. Quality-based purchasing policy is a method that allows wheat quality characteristics to be determined with various devices in a short time. This method, which is decisive in quality classification and product pricing scale, must be explained correctly to producers. Otherwise, the producer ’s trust in the TGB may gradually decrease. This can be achieved through initiatives taken by the institution or through various publications and training activities. One of the most important results of this study is that TGBs and decision-makers are more sensitive to local producers. For decision-makers to maintain their influence on the producer, they must carefully examine the details of the processes with an inductive approach, starting from the bottom up. This situation is considered critical in terms of food security.